Pop-Up Book Media on Animal Life Cycle Topic - Ni Made Radha Dwi Goestiani; I Made Citra Wibawa; Ni Wayan Rati (Universitas Pendidikan Ganesha, 2021)
The lack of teacher creativity in developing learning media that is by the characteristics of students makes learning less than optimal. Therefore, it is necessary to develop suitable media in learning. The purpose of this study was to develop a pop-up book on the topic of animal life cycles. This type of research is development research. The model used is ADDIE. The subject of this research is one material, design, media expert, two practitioners, and five students. The methods used to collect data are observation, interviews, and questionnaires. The instrument used to collect data is a questionnaire. The method and instrument used is the twig scale. The technique used in analyzing the data is descriptive qualitative and quantitative analysis. The analysis results show that the developed pop-up book media received excellent qualifications from experts and students. So, the pop-up book media on animal life cycles deserve to be used with excellent qualifications in the learning process. This research implies that pop-up book media can be used to increase science learning knowledge.